The Effect of Intensity of Social Media Usage and Perceptions Regarding the Palestine People's War on Students' Concern - Mattotorang, Shakila Salwa; Subardjo, Ratna Yunita Setiyani (Journal of Health Sciences and Medical Development, 2024)
This research aims to determine the influence of the intensity of social media use on perceptions and concerns about the war that occurred in Palestine. The method used in this research is quantitative methods by collecting data from the results of questionnaires that have been distributed. The analysis was carried out using the Microsoft Excel application and the SPSS application to find the results. The results of the research show that the intensity of social media use influences students' perceptions and concerns regarding the war taking place in Palestine. With a P value < 0.05. It is hoped that this research will provide insight to readers, researchers, or practitioners in understanding the role of social media and its influence.